2011
DOI: 10.1590/s1806-66902011000100017
|View full text |Cite
|
Sign up to set email alerts
|

Análise de trilha do rendimento de grãos de feijoeiro (Phaseolus vulgaris L.) e seus componentes

Abstract: Resumo -C i nqüenta e oito genótipos de feijoeiro (Phaseolus vulgaris L . ), sendo 32 genótipos locais, 20 genótipos provenientes da EMBRAPA e seis cultivares comerciais, foram avaliados em Alegre/ES, através da influência de oito caracteres de importância agronômica sobre a produção de grãos por unidade de área. O experimento, em blocos casualizados com três repetições, foi conduzido no período das "águas" no ano agrícola de 2008/09. O objetivo deste trabalho foi estimar os coeficientes de trilha entre os car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 15 publications
7
30
1
13
Order By: Relevance
“…The X, Y, and Z primary components have positive and strong genetic and phenotypic correlations with grain yield (Cabral et al, 2011;Zilio et al, 2011;Ribeiro et al, 2014), an observation that was supported by the results of the current study (Table 3). However, the correlations were negative or weak between X and Y, X and Z, and Y and Z.…”
Section: Discussionsupporting
confidence: 87%
“…The X, Y, and Z primary components have positive and strong genetic and phenotypic correlations with grain yield (Cabral et al, 2011;Zilio et al, 2011;Ribeiro et al, 2014), an observation that was supported by the results of the current study (Table 3). However, the correlations were negative or weak between X and Y, X and Z, and Y and Z.…”
Section: Discussionsupporting
confidence: 87%
“…In a study conducted by Ribeiro et al (2001), carioca bean genotypes showed a negative genetic correlation between the cycle and grain yield, weight of 100 grains, number of pods and grains per plant, and number of grains per legume. Cabral et al (2011) also observed a negative correlation between the yield and emergence-flowering and emergenceharvest periods. According to Rocha and Vello (1999), soybean grain yield varied with maturity cycle and cultivation location: short-cycle, semi-short-cycle and mediumcycle genotypes demonstrated greater grain yields than late-cycle varieties.…”
Section: Resultsmentioning
confidence: 78%
“…According to Cabral et al (2011), plants with a lower number of days between emergence and flowering and between flowering and physiological maturity produce a greater number of pods per plant, seeds per pod and weight of 100 seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atualmente, a análise de trilha é amplamente utilizada por melhoristas de plantas, em diversas culturas como o milho (AGRAMA, 2006), o feijão (CABRAL et al, 2011), o arroz (MARCHEZAN et al, 2005, o algodão (HOOGERHEIDE et al, 2007), a soja (BÁRBARO et al, 2006) e o trigo (GONDIM et al, 2008). Estudos sobre relações entre variáveis importantes para a cultura da cana via análise de trilha também são encontrados na literatura (KANG et al, 1983;REDDY & REDDI, 1986;SUKHCHAIN & SAINI, 1997;FERREIRA et al, 2007;SILVA et al, 2009).…”
Section: Introductionunclassified